The North Atlantic Oscillation influence on the Debeli Namet Glacier - Gordana Jovanović (Acta Geographica Slovenica, 2023)
This article presents the relationship between climate variables in the Durmitor Massif (Montenegro) and the North Atlantic Oscillation (NAO). A new climate standard for temperatures and precipitation over the last 30 years has been presented. The Debeli Namet Glacier is an indicator of climate change. We have shown that the size of this glacier is affected by the NAO which mainly affects the precipitation in the accumulation period from December to March. During the ablation period from June to September, the influence of the NAO on precipitation and temperatures is less pronounced. El Niño and La Niña events are significant, especially in years with a low NAO index. The relationship between El Niño/La Niña and the NAO is still a subject of scientific debate.